Can collaboration between local authorities enable efficent and effective environmental management? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Resource and Environmental Planning at Massey University, Manawatu, New Zealand - McSoriley, Luke Gerard (Massey University, 2012)
Local authorities in New Zealand are under increasing pressure from central government and the public to deliver efficient and effective local government. Local authorities are required to operate in a fiscally efficient manner while also undertaking a range of local government functions effectively. Local authority collaboration has been identified as a useful approach to the delivery of local government functions that can achieve efficiencies while also providing for effective local government. Local authority collaboration has also been identified as an alternative or complimentary approach to local authority amalgamation. Regulatory functions associated with environmental management are a key responsibility of local governments in New Zealand. This research evaluates the value and efficacy of local authority collaboration in environmental management. The primary research method was a case study of a Southland example of local authority collaboration in environmental management. The secondary research method was a documentary analysis of eight other New Zealand examples of inter-council collaboration in environmental management. The theory and practice of collaboration between local governments was also analysed through a review of relevant literature. This research has shown that collaboration between local governments can be fiscally efficient, whilst also providing an effective approach to the management of environmental issues. The research has also shown that local authority collaboration in environmental management can be effective across a range of environmental issues. The research concludes that local authority collaboration is a valuable and efficacious approach that can enable effective and efficient environmental management.
Keywords: Local government, New Zealand; Local authority collaboration; Environmental management, New Zealand